Efficacy and safety of dalbavancin in the treatment of acute bacterial skin and skin structure infections (ABSSSIs) and other infections in a real-life setting: data from an Italian observational multicentric study (DALBITA study). Issue 12 (1st December 2020) - Bai, Francesca; Aldieri, Chiara; Cattelan, AnnaMaria; Raumer, Francesca; Di Meco, Eugenia; Moioli, Maria Cristina; Tordato, Federica; Morelli, Paola; Borghi, Federica; Rizzi, Marco; Van Hauwermeiren, Evelyn; Castelli, Francesco; et al.
ABSTRACT: Objectives: We evaluated the efficacy and safety of dalbavancin in ABSSSI and 'other sites' infections' (OTA). Methods: Observational study involving 11 Italian hospitals including patients that received ≥1 dose of dalbavancin in 2016–2019. The outcome was end-of-treatment efficacy and safety in ABSSSI and OTA in a real-life setting. Results: 206 patients enrolled (males 50%, median age 62 [IQR 50–76] years), 60.2% ABSSSI, 39.8% OTA. 69.7% ABSSSI vs 90.7% OTA (p = 0.003) and 46.3% ABSSSI vs 37.2% OTA (p = 0.786) received previous and concomitant antibiotics, respectively. 82.5% reached clinical cure . Eleven (5.4%) patients had non-serious adverse events (AE). OTA patients showed longer hospitalization (13.5 days, 5.5–22 vs 3, 0–11.7; p<0.0001) and received longer previous (18 days, 9–30 vs 11, 7–19; p = 0.007)/concomitant antibiotic treatments (21 days, 14–52 vs 11, 8–14; p < 0.0001), compared to ABSSSI. ABSSSI and OTA showed similar efficacy (85.5% vs 75%, p = 0.459) and safety (no AE: 81.5% vs 64.3%, p = 0.258); efficacy was independent of previous/concomitant therapies. Conclusions: Dalbavancin demonstrated a success rate of >80%, with similar efficacy/safety in ABSSSI and off-label indications. The preferential use of dalbavancin as second-line or combination therapy would seem to suggest the need for in-depth studies focused on its off-label use.